2013
DOI: 10.1007/s11427-013-4580-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in a multicellular green alga Volvox carteri

Abstract: microRNAs (miRNAs) have emerged as key components in the eukaryotic gene regulatory network. We and others have previously identified many miRNAs in a unicellular green alga, Chlamydomonas reinhardtii. To investigate whether mi-RNA-mediated gene regulation is a general mechanism in green algae and how miRNAs have been evolved in the green algal lineage, we examined small RNAs in Volvox carteri, a multicellular species in the same family with Chlamydomonas reinhardtii. We identified 174 miRNAs in Volvox, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…This also appears to be the case for some miRNAs in both C. reinhardtii and V. carteri, where expected target RNA cleavage products have been experimentally detected (Molnar et al, 2007;Zhao et al, 2007;Li et al, 2014;Voshall et al, 2014). Yet, very few of the reported Chlamydomonas or Volvox miRNAs have identifiable targets with near perfect complementarity (Molnar et al, 2007;Li et al, 2014;Voshall et al, 2014) and recent evidence suggests that miRNA regulation of transcript expression in Chlamydomonas may operate, at least for certain targets, by translation repression (Ma et al, 2013;Yamasaki et al, 2013;Voshall et al, 2014).…”
Section: Biological Role(s) Of Rna Interferencementioning
confidence: 59%
See 3 more Smart Citations
“…This also appears to be the case for some miRNAs in both C. reinhardtii and V. carteri, where expected target RNA cleavage products have been experimentally detected (Molnar et al, 2007;Zhao et al, 2007;Li et al, 2014;Voshall et al, 2014). Yet, very few of the reported Chlamydomonas or Volvox miRNAs have identifiable targets with near perfect complementarity (Molnar et al, 2007;Li et al, 2014;Voshall et al, 2014) and recent evidence suggests that miRNA regulation of transcript expression in Chlamydomonas may operate, at least for certain targets, by translation repression (Ma et al, 2013;Yamasaki et al, 2013;Voshall et al, 2014).…”
Section: Biological Role(s) Of Rna Interferencementioning
confidence: 59%
“…C. reinhardtii has been shown to contain a complex set of endogenous sRNAs including miRNAs, phased siRNAs, as well as siRNAs originating from transposons and repeated DNA regions (Molnar et al, 2007;Zhao et al, 2007;Yamasaki et al, 2013;Voshall et al, 2014). Likewise, V. carteri has been demonstrated to possess miRNAs, many of them being preferentially enriched in either gonidia or somatic cells (Li et al, 2014). Interestingly, there appears to be little conservation of miRNA genes among algal species or with those encoded in the genomes of land plants or animals (Cerutti et al, 2011;Li et al, 2014;Voshall et al, 2014).…”
Section: Phylogenetic Analysis and Domain Organization Of Core Componmentioning
confidence: 99%
See 2 more Smart Citations
“…microRNAs (miRNAs, miRs), through a combination of translational blockade and/or mRNA degradation, have been widely reported to possess the potential to regulate pathological and physiological processes [7], including proliferation, differentiation, death, metabolism and oxidative stress. It is currently believed that thousands of classic (protein-encoding) genes are controlled via such mechanisms; furthermore, it has been shown that some miRNAs tend to be associated with some special functional regulatory mechanisms [8], such as miR-146a for inflammatory response [9] and miR-126 for angiogenesis modulation [10].…”
mentioning
confidence: 99%